The Influence of Transformational Leadership Style, Work Commitment, and Organizational Citizenship Behavior (OCB) on Teacher Performance Through Job Satisfaction as an Intervening Variable: (Study at the Maria Fatima Jember SDK Education Unit) - Veronika Suhartati; Sri Wahyu Lelly Hana Setyanti; Dewi Prihatini (Institut Teknologi dan Bisnis (ITB) Semarang, 2024)
This research aims to examine and analyze the influence of transformational leadership, work commitment, organizational citizenship behavior (OCB), on teacher performance through job satisfaction as an intervening variable in the Maria Fatima Jember Elementary School education unit. The variables in this research are Transformational Leadership, Work Commitment, Organizational Citizenship Behavior (OCB), Teacher Job Satisfaction and Teacher Performance. The population and sample in this research were all teachers at SDK Maria Fatima Jember, East Java, totaling 60 teachers and the sample in this research was 60 teachers. The number of samples is the same as the population because the number is less than 100. The data collection method uses a questionnaire. Data analysis in research uses the SEM-PLS method using SmartPLS software. The research results show that there is a significant influence between Transformational Leadership, Organizational Citizenship Behavior (OCB) and job satisfaction on Teacher Performance. Meanwhile, work commitment has no effect on teacher performance. And job satisfaction is able to mediate transformational leadership, work commitment, Organizational Citizenship Behavior.